2010
DOI: 10.1002/cctc.201000046
|View full text |Cite
|
Sign up to set email alerts
|

Amination of Aliphatic Alcohols and Diols with an Iridium Pincer Catalyst

Abstract: Best aminated feature: Catalytic transformation of alcohols to amines is a fundamental transformation in synthetic organic chemistry. A general salt‐free Ir‐catalyzed amination of aliphatic alcohols and diols has been developed, which gives amino alcohols with high selectivity. By use of an Ir–pincer chlorodihydride complex, usually applied for the transfer hydrogenation of ketones, simple monoalcohols are aminated with excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…The most desirable situation is that in which the reaction is performed under base‐free conditions. Remarkable reports have been made by the groups of Gusev, Milstein, Hanson, Kempe, Börner, and Sun and Liu . Figure shows some representative examples of catalysts for the dehydrogenative coupling of alcohols with amines.…”
Section: Dehydrogenation Reactionsmentioning
confidence: 96%
“…The most desirable situation is that in which the reaction is performed under base‐free conditions. Remarkable reports have been made by the groups of Gusev, Milstein, Hanson, Kempe, Börner, and Sun and Liu . Figure shows some representative examples of catalysts for the dehydrogenative coupling of alcohols with amines.…”
Section: Dehydrogenation Reactionsmentioning
confidence: 96%
“…An iridium pincer catalyst has been reported by Börner, where the reaction proceeded with almost perfect selectivity but the use of excess amine was required; nevertheless, ethylene glycol is usually less expensive than amine substrates. 7 A heterogeneous catalyst using Pd/C and an excess amount of ZnO has been developed, but only the hydroxyethylation of tetrahydroquinoline was examined, and only 50% yield of amino alcohol product was obtained because of the formation of undesired tricyclic by-product. 8 Over the course of studies on our ruthenium-catalyzed borrowing hydrogen reactions using ethylene glycol for the construction of amino alcohols 9 and cyclic compounds, 10 we found that the RuCl2(PPh3)3/Xantphos catalyst is effective for the representative and highly selective formation of -amino alcohols by the reaction of cyclic amines and ethylene glycol.…”
Section: Figure 1 Examples Of In Approved Drugs Including N-(hydroxymentioning
confidence: 99%
“…Hence, the bis(phosphinoethane)amine M(PNP) fragment both exhibits typical reactivity for Noyori‐type MLC catalysts and represents an aliphatic analogue of Milstein’s system. Ruthenium, osmium and iridium complexes with this ligand were used as catalysts for ketone DH and TH,43b, 51, 80, 81 acceptorless alcohol dehydrogenation and dehydrocoupling,44b,c,d,e borane‐amine dehydrocoupling,79, 95 and borane‐amine hydrolysis 82. Mechanistic examinations of the dual H 2 elimination/addition sequence suggest that the imine complex 11 is an unstable intermediate towards both migrative imine insertion and hydrogen loss 83.…”
Section: Bio‐inspired Homogeneous Catalysis: Metal‐ligand Cooperatmentioning
confidence: 99%